Quelques commentaires sur le rapport de l 'Office de revision du Code civil sur le droit international privé - Deleury, Edith; Prujiner, Alain (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1977)
This comment of the "Report on Private International Law" prepared by the Private International Law Committee of the Civil Code Revision Office is in answer to the Committee's request for voiced reactions to its project. The comments follow the draft's order and constitute, after a short survey, a series of remarks and suggestions for improvement.